Syllabification in Indonesian Language - Sujarno, Sujarno (Budapest International Research and Critics University, 2021)
Dictionary cannot be separated with syllabification because it is one of the crucial parts of the reference book. It has been widely known that each language has its own linguistic system which creates differences between one language to another; and one of those differences is the system of syllabification. Syllabification, in Indonesian language system owns different rules compared to other languages. The practice of syllabification for Indonesian words considers the structure of the vowels and the consonants, as well as the syllabic itself, and the other rules of syllabification.